Business Strategy, Corporate Governance, Firm Characteristics, and Risk Disclosure in the Indonesian Stock Exchange - Nadhilla Mazaya; Fuad Fuad (Jurnal Keuangan dan Perbankan, 2018)
Companies were required to disclose non-financial information other than financial statements, due to the rapid and changing business conditions. This study aimed to examine the impact of business strategy, corporate governance, and firm characteristics on the risk disclosure. More specifically, we examined the impact of barriers to entry, cost leadership, the board of commissioner size, ownership concentration, liquidity, industrial profile, and auditor type on risk disclosure. We used a sample consisted of 96 observations for the period of 2008-2015 listed in Indonesian Stock Exchange and PEFINDO 25. This research conducted using multiple regression analysis methods to examine the factors influenced risk disclosure. This research also used independent sample T-test to investigate the quality of risk disclosure before, and after the implementation of IFRS in Indonesia, We found that barriers to entry, the board of commissioner size, ownership concentration, industrial profile, and auditor type significantly affect the risk disclosure. However, cost leadership and liquidity did not have significant effects on the risk disclosure. Results of the study might provide a sound contribution for further research, government, management of the company, and investors regarding the risk disclosure practices.JEL Classifications: G32, G34DOI: https://doi.org/10.26905/jkdp.v22i3.2167